Probabilistic stability analysis of soil nailed vertical excavation using Monte Carlo simulation (MCS). (2022) - Muthukumar, Surya; Sathyan, Dhanya; Shukla, Sanjay Kumar
Abstract: Soil nailing is considered as one of the widely used excavation retaining systems to reinforce and strengthen the soil surface in terms of stability. It provides resistance against the deformation of the wall and improves the overall stability along the soil interface, resulting in improved performance under seismic conditions. The soil nail walls are analyzed mostly using the conventional limit equilibrium approaches. Pseudo-static and pseudo-dynamic methods consider the effect of earthquake acceleration to analyse the stability. However, these methods also had some constraint that includes the dissatisfaction of no stress boundary condition. The deterministic approach towards any earth retaining structure is not reliable and also uneconomical since it produces inaccurate results on stability analysis with a specific value as safety factor. This happens because it does not calculate the uncertainty of the influencing parameters on determining the factor of safety. As a result, in this study, the probabilistic analysis is executed to forecast the realistic failure probability of soil nailed wall. To perform probabilistic analysis, many aspects are needed for the study such as influence and effect of various parameters on achieving soil stability, and significance of safety factor in case of different modes of failure. The probability of failure ( Pf ) of nailed wall is estimated by Monte Carlo simulation (MCS), which is a powerful tool for stability analysis performed using the software MINITAB. This simulation method reflects realistic conditions of problem than the conventional method of stability analysis based on safety coefficients. From the results of the simulation, it is found that the probability of failure decreases with an increase in pullout capacity, axial force, and tensile capacity of the nail.